Effect on the performance test towards flow controller and level controller using Zieglar Nichols tuning rule / Nurhafizah Mohd Safie - Mohd Safie, Nurhafizah (2018)
The project is relies on step input change of level control process and also flow control process and the step change must between ±10%. Level control (LIC11) DeltaV operate system and also flow control (FIC21) DeltaV operate system are demonstrate at process control laboratory located in pilot plant UiTM Shah Alam. The method used consist of open loop tuning and also a close loop tuning. The results express different values in term of settling time and the values needed for closed loop tuning method. The basic of process control is, when all of four block are connected the process control loop is called close loop system and when any of the blocks is disconnected the process control loop is called open loop system. In the close loop system, the controller compares the process measurement signal (PV) from set point (SP) and make necessary corrective action to the final control element. In open loop system, the controller has no control over the final control element therefore, the adjustment is made manually by operator.